Paraneoplastic ophthalmoplegia and subacute motor axonal neuropathy associated with anti-GQ1b antibodies in a patient with malignant melanoma. Issue 4 (1st April 2003) - Kloos, L; Sillevis Smitt, P; Ang, C W; Kruit, W; Stoter, G
Abstract : A 68 year old woman developed oculomotor paresis shortly after metastatic progression of her melanoma was discovered. She was then immunised with the tumour antigen MAGE-3 in combination with an immunological adjuvant. During immunisation her symptoms worsened and she developed severe, predominantly proximal axonal motor neuropathy and became bedridden. IgM antibodies against gangliosides GM2, GD3, and GQ1b were detected in serum obtained two weeks before and nine weeks after the onset of symptoms. Immunohistochemically, the patient's IgM reacted with the tumour and co-localised with GQ1b. She improved neurologically following steroid treatment and became ambulatory.